唐代传奇中的女性形象 = The womens' role during the Tang Dynasty as portrayed in "Tang Chuanqi" (short stories of Tang Dynasty) - 胡月宝 Aw, Guat Poh (2009)
Tang Chuanqi is an important literature creation in ancient China . As compared to the Pre-Tang literature , Tang Chuanqi has created quite a number of women with speciflc role . It is indeed very special in a man dominated society like ancient China . Therefore , it is interesting to look into the womens' role of Tang Dynasty as portrayed in Tang Chuanqi.